(untitled) (Academic Journal of International University of Erbil, 2025)
The focus of this study was to investigate the role of authentic leadership on enhancing organizational trust in college and institutes in Soran independent administration in KRI. The main objective of this research is to investigate the role of authentic leadership and its dimensions on enhancing organizational trust. A Descriptive method using quantitative technique (questionnaires) was employed to collect data from 183 academic staffs from 13 college and institutes in Soran independent administration in KRI. The study's findings highlight the crucial role of authentic leadership in fostering and cultivating organizational trust among academic staff. The results also confirmed that there is a significant correlation between authentic leadership and its dimensions (relational transparency, internal moral perspective, self-awareness, balance processing, and social-awareness), and organizational trust as a whole, furthermore the research shows that the impact of authentic leadership and its dimensions on organizational trust among academic staff statistically is significant, and balance processing has the greatest influence to make the academic staff to feel trust in their college and institutes. Finally, it is advisable to pursue qualitative method in the future, broadening the focus to include different groups such as employees in colleges and institutes. This approach will yield more comprehensive research findings and provide detailed insights.